Exploring Grade 12 Biology teachers' conceptions, dispositions and pedagogic strategies when mediating learning of evolution in Namibia - Katuuo, Henry U (Rhodes University, Faculty of Education, Department of Education, 2017)
The Namibian Senior Secondary Certificate Examiners' Reports (2013) shed light on the topics in which learners often perform poorly and evolution is one of such problematic topics. Anecdotal reasons include religious views of teachers, opposition by learners to the topic, and inadequate understanding of the subject content knowledge. I have not come across any literature on evolution in Namibia that formally look closely at this problem. We do not have a clear idea of what is going on in Namibian science classrooms, when evolution is taught. We do not have a clear idea of the factors at play in the teaching of evolution in these classrooms, either when it is done well and completely or when it is not so. It is against this background that I was inspired to engage in this study which examined teachers' conceptions, dispositions and pedagogical strategies that they use when teaching evolution. The study is underpinned by an interpretive paradigm, which afforded me an opportunity to understand the teachers' worldviews in relation to evolution. It also allowed me to gain insight on the pedagogical strategies that teachers use when mediating learning of the topic of evolution and its related concepts. Within the interpretive paradigm, a case study approach was adopted, using a mixed-method design generating both quantitative and qualitative data. Teachers from two regions, namely, the Hardap region and Khomas region, participated in the study. Data were generated using questionnaires, semi-structured interviews and lesson observations. Fifteen questionnaires were completed and from those questionnaires, the sample included six teachers (40%) from the Hardap region while nine teachers (60%) were from the Khomas region. For the interview, the sample included two teachers - one from each region. For the observations, I observed five teachers teaching evolution. I presented quantitative data in tables and graphs, whereas the qualitative data was analysed inductively using Vygotsky's (1978) socio-cultural theory as a theoretical framework. In addition, I used Ogunniyi's (2006) Contiguity Argumentative Theory (CAT) as an analytical framework. These theories were used as lenses to interpret and make sense of the qualitative data, which I colour coded to form sub-themes. Thereafter, overlapping sub-themes were combined to form themes, which were linked to the research questions and in relation to literature/theory. Similarly, overlapping themes were combined to form analytical statements. It emerged from the study that religious views did not play a large role in most teachers' views and attitudes towards the teaching of evolution. Instead, it emerged that lack of content knowledge on evolution is the main factor that influences teachers' views and attitudes towards teaching evolution in schools. This is quite profound, as the assumption is that when teachers are religious, the likelihood is that they would object to the teaching of evolution. In light of this, the study recommends that there is a need for professional development and support of science teachers, so that they are able to properly mediate the learning of evolution.
Keywords: Biology teachers -- Attitudes -- Namibia; Biology teachers -- Training of -- Namibia; Evolution -- Study and teaching -- Namibia